A mixed-methods evaluation of the impacts of an online Carer wellbeing and connection program - Amy Coe; Jennifer Bibb; Roxanne Kritharidis; Mary O'Mara; Rebekah Lautman; Konstancja Densley; Sarah Kovarik; Catherine Kaylor-Hughes; Matthew Lewis; Victoria J. Palmer (Elsevier, 2023)
Objective: To evaluate a facilitated, 90-min session, delivered for four weeks, Online Carer Wellbeing and Connection Program in Victoria, Australia. Methods: One hundred and three carers took part in the evaluation. Eighty-six completed both pre- and post-program surveys evaluating program impacts on psychological distress, perceived loneliness, and social support. Qualitative interviews were conducted (n = 76) post-program for experiential data. Findings: Paired samples t-tests showed significant decreases between pre- and post-program for psychological distress (M = 25.10, SD = 7.08; M = 22.00, SD = 6.57; t(85) = 4.88, p = 0.000), perceived loneliness (M = 6.69, SD = 1.89; M = 6.14, SD = 1.76; t(85) = 3.45, p = 0.000) and perceived social support (M = 8.31, SD = 2.48; M = 8.83, SD = 2.21; t(85) = −2.54, p = 0.013). Thematic analysis identified positive experiences and the mechanisms of action (or the ingredients for program success) as: 1. Delivery by a trained facilitator; 2. Provision of respite for person being cared for during meetings; 3. Technical assistance; 4. Online modality; 5. Inclusivity; 6. Diversity of experience; 7. Shared understanding; 8. Safety; 9. Emotional release; 10. Reflection, and; 11. Self-care practices. Innovation: A model illustrating the mechanisms of action based on the findings of the mixed-methods evaluation is presented to support wider implementation and translation. Conclusion: The online program effectively reduced psychological distress and loneliness and improved carer wellbeing.